Frequency Selective Properties of Coaxial Transmission Lines Loaded with Combined Artificial Inclusions - Francisco Falcone; Javier Gil (The Scientific World Journal)
The properties of a modified coaxial transmission line by periodic inclusions will be discussed. The introduction of split ring resonators, conductor stubs, air gaps, and combination of these gives rise to new frequency selective properties, such as stopband or passband behavior, observable in planar as well as volumetric metamaterial structures. These results envisage new potential applications and implementation of devices in coaxial transmission line technology.